Representing/Roma/Holocaust: Exhibition Experiences in Europe and East Asia (Critical Romani Studies, 2022)
This article reflects on two exhibitions, in 2018 and 2019, about the Nazi persecution of German Sinti and Roma. One was produced by an Anglo-German curatorial team and toured Britain and Continental Europe. The second was designed by South Korean curators and installed temporarily in a gallery in downtown Seoul. The two exhibitions drew on the same photographic archive, narrated the persecution histories of Romani subjects of the photographs, and used the story of their relationship with the non-Romani photographer to ask questions about responsibility and to prompt visitors to reflect on their own status as “implicated subjects” in contemporary forms of discrimination. Given different expectations of the level of knowledge that visitors bring to the exhibition and different communicative tools familiar to them (the Seoul curators included creative artists), the two curatorial teams took very different approaches to informing and moving their audiences – and to meeting the recognized challenges of representing Romani history and identity – not least in the ways in which the exhibition’s message was mediated in face-to-face conversations on site. The aesthetic approach adopted in Seoul did not fully succeed in maintaining the balance between explanation and exoticization. The evaluation relies on visitor surveys (quantitative and qualitative) and interviews with guides.
Keywords: Exhibition; Holocaust; Genocide; Memory; Photography